Necrosis of gallbladder polyp: Report of two cases - Tanaka, Masao; Mori, Yasuhisa; Yamaguchi, Koji; Konomi, Hiroyuki; Tanabe, Reiko; Nakamura, Masafumi; Watanabe, Masato; Nagate, Shigenori (Tando, 2005)
Necrosis is a rare phenomenon of gallbladder polyps. Two cases of gallbladder polyp with necrosis are reported. Case 1: A 76-year-old woman was admitted to examine an elevated lesion of the gallbladder on US. MRI revealed an elevated lesion in the fundus of the gallbladder, measuring 4.0 to 5.0 cm and showing high intensity on T 1 W 1 and low intensity on T 2 W 1. Laparoscopic cholesystectomy was performed. Pathological diagnosis was a benign polypoid lesion which was almost completely necrotic. Case 2: A 61-year-old man was pointed out as having a gallbladder polyp, measuring 19× 18 mm on US and he was referred for further emamination. MRI showed a high intensity area at the surface of gallbladder tumor on T 1 W 1. Hepatectomy (S 4 a + S 5) and extrahepatic bile duct resection was performed. Macroscopically, the surface of the gallbladder tumor was necrotic and pathological diagnosis was adenocarcinoma with superficial necrosis.